Analisa Prediksi Kebangkrutan Perusahaan (Financial Distress) Menggunakan Metode Altman Z-Score Pada BPR Dan BPRS Kota Dan Kabupaten Tasikmalaya Jawa Barat 2019 – 2023 - Dim Zarita Suryanugraha; Noneng Masitoh (AKUNTANSI 45, 2025)
Corporate bankruptcy is rarely sudden, it often arrives with warning signs that go unnoticed. This study analyzes financial vulnerability in 11 BPR and BPRS in Tasikmalaya by applying the Altman Z-Score model during the 2019–2023 period. The findings reveal that three institution fell into the distress zone in 2023. The decline in Z-Scores was triggered by key financial variables such as negative operating income (EBIT), negative retained earnings, and decreased net working capital. These results present strategic implications not only for internal management, but also for regulators such as the Financial Services Authority (OJK), and the wider public as financial service users. Through a descriptive quantitative approach, this research confirms that early detection of bankruptcy is not only possible but urgent, in order to safeguard the stability of micro-financial institutions and support sustainable regional economic development.